What role does touch play in active entertainment? A narrative review of tactile feedback in gaming - Yang Gao; Charles Spence (i-Perception)
This narrative literature review explores the role of tactile stimulation within interactive gaming and storytelling. Focusing on active entertainment experiences—where the audience/player has some control over what happens, unlike passive media such as film. The review traces tactile/haptic feedback from the 18th century electric-shock amusements to contemporary vibrotactile controllers and interactive cinema. The review also highlights touch's potential to enhance interactivity across active entertainments. Key themes include the role of touch in active versus passive forms of entertainment. In the context of active entertainment, audience participation influences the gameplay/plot, while in passive entertainment, the audience simply observes without being able to alter the outcome. The review also contrasts first- and third-person viewer perspectives and the viewpoint specificity of much tactile/haptic stimulation, particularly concerning these perspectives. Additionally, the review discusses the technical challenges associated with much of the wearable haptic technology that has been introduced to date, and consumer preferences and willingness to pay for haptic devices and enhanced haptic (broadly referring to any kind of tactile) experiences. The review concludes by emphasizing the multifaceted roles of haptic feedback in gameplay, narrative enhancement, and emotional engagement. It also suggests directions for future research to expand the potential of touch within multisensory entertainment.